Impact of D-STATCOM Placement on Improving the Reactive Loading Capability of Unbalanced Radial Distribution System. (2016) - Gupta, Atma Ram; Kumar, Ashwani
Abstract: In this paper, Distribution STATic COMpensator (D-STATCOM) are optimally placed in unbalanced radial distribution systems (UBRDS) using sensitivity approaches with an objective of improving the reactive loading capability of the network with maintaining voltage profile in an acceptable limit. Optimal locations of D-STATCOM are determined using Voltage Stability Index (VSI). Optimum size of D-STATCOM is obtained by variational algorithm subjected to minimization of total power loss. In order to quantitatively analyze the impact of D-STATCOM on voltage stability margin, Q-V curves are drawn using continuation power flow method. In this study the impact of D-STATCOM placement is investigated for large industrial load model with light, medium and high loading conditions. Also, load growth scenario is considered for better planning of the system. The results are obtained on standard 25-bus and IEEE-37 bus UBRDS to verify the practicability of proposed methodology.